2006
DOI: 10.1590/s0074-02762006000900027
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial artificial chromosome library for Biomphalaria glabrata, intermediate snail host of Schistosoma mansoni

Abstract: To provide a novel resource for analysis of the genome of Biomphalaria glabrata, members of the international Biomphalaria glabrata Genome Initiative (biology.unm.edu/biomphalaria-genome.html Key words: genomics -gene discovery -fingerprinting -schistosomiasis -medical malacologyThe application of molecular approaches continues to contribute novel insights into the biology, including genomics of molluscs . To date, several mitochondrial genomes of molluscs have been sequenced (DeJong et al. 2004, Mizi et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
(49 reference statements)
1
33
0
Order By: Relevance
“…The distribution of B. glabrata largely defines the areas that are endemic for schistosomiasis in South and Central America (Dejong et al, 2003), but only a low proportion of snails in the field is patently infected with schistosomes (de Souza et al, 1994) and some B. glabrata are naturally resistant (Paraense and Correa, 1963). Increasingly, experimental study of B. glabrata as intermediate host of schistosomes and related digenetic trematode parasites incorporates characterization of the genome (Adema et al, 2006;DeJong et al, 2004;Raghavan and Knight, 2006), the proteome (Bouchut et al, 2006b;Vergote et al, 2005) and especially the transcriptome (Bouchut et al, 2006a;Jung et al, 2005;Knight et al, 1999;Lockyer et al, 2007a;Lockyer et al, 2007b;Miller et al, 2001;Mitta et al, 2005;Nowak et al, 2004;Raghavan et al, 2003) …”
Section: Introductionmentioning
confidence: 99%
“…The distribution of B. glabrata largely defines the areas that are endemic for schistosomiasis in South and Central America (Dejong et al, 2003), but only a low proportion of snails in the field is patently infected with schistosomes (de Souza et al, 1994) and some B. glabrata are naturally resistant (Paraense and Correa, 1963). Increasingly, experimental study of B. glabrata as intermediate host of schistosomes and related digenetic trematode parasites incorporates characterization of the genome (Adema et al, 2006;DeJong et al, 2004;Raghavan and Knight, 2006), the proteome (Bouchut et al, 2006b;Vergote et al, 2005) and especially the transcriptome (Bouchut et al, 2006a;Jung et al, 2005;Knight et al, 1999;Lockyer et al, 2007a;Lockyer et al, 2007b;Miller et al, 2001;Mitta et al, 2005;Nowak et al, 2004;Raghavan et al, 2003) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because these markers were developed based on expressed sequences, we hope a novel gene silencing RNA interference (RNAi) soaking method that we have recently developed (Knight et al, 2011b) will help to reveal the function of these identified genes as linked to B. glabrata susceptibility and resistance to S. mansoni infection. In addition, using the cloned markers as probes, corresponding bacterial artificial chromosomes (BACs) have now been identified and are currently being utilised (Adema et al, 2006) for the physical mapping of ex vivo B. glabrata chromosomes (Odoemelam et al, 2009, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…To better qualify for full genome sequencing, some research communities developed complementary genomic resources. Bacterial artificial chromosome (BAC) libraries were developed for several molluscs like B. glabrata (Gastropda) and the oysters Crassostrea virginica and C. gigas , to gain initial access to genomic information (Adema et al, 2006; Cunningham et al, 2006; Raghavan et al, 2007). BAC libraries consist of considerable numbers of clones that represent the full genome with large (>100kb) inserts of molluscan genomic DNA.…”
Section: Genomes and Next-generation Sequencing Immunogenomics Phmentioning
confidence: 99%